Kirkpatrick evaluation model for in-service training on cardiopulmonary resuscitation - Safoura Dorri; Malekeh Akbari; Mahmoud Dorri Sedeh (Wolters Kluwer Medknow Publications, 2016)
Background: There are several evaluation models that can be used to evaluate the effect of in-service training; one of them is the Kirkpatrick model. The aim of the present study is to assess the in-service training of cardiopulmonary resuscitation (CPR) for nurses based on the Kirkpatrick's model. Materials and Methods: This study is a cross-sectional study based on the Kirkpatrick's model in which the efficacy of in-service training of CPR to nurses was assessed in the Shahadaye Lenjan Hospital in Isfahan province in 2014. 80 nurses and Nurse's aides participated in the study after providing informed consent. The in-service training course was evaluated in reaction, learning, behavior, and results level of the Kirkpatrick model. Data were collected through a researcher-made questionnaire. Results: The mean age of the participants was 35 ± 8.5 years. The effectiveness score obtained in the reaction level (first level in the Kirkpatrick model) was 4.2 ± 0.32. The effectiveness score in the second level of model or the learning level was 4.70 ± 0.09, which is statistically significant (P < 0.001). The effectiveness score at the third and fourth level were 4.1 ± 0.34 and 4.3 ± 0.12, respectively. Total effectiveness score was 4.35. Conclusions: The results of this study showed that CPR in-service training has a favorable effect on all four levels of the Kirkpatrick model for nurses and nurse's aides.